PREDICTING OPIOID OVERDOSE RISK IN OLDER ADULTS DISCHARGED FROM THE EMERGENCY DEPARTMENT. (16th November 2018) - Sheikh, S; Norse, A; Henson, M; Dodd, C; Kalynych, C; Smotherman, C; Hendry, P
Abstract: Over 25 million opioid prescriptions were filled by US adults ≥ 55 years in 2016. Opioid overdose in now a leading cause of death in the US. The Risk Index for Overdose or Serious Opioid-induced Respiratory Depression (CIP-RIOSORD) is a validated tool that calculates a risk class (highest risk class for overdose is 7) for a patient's probability of experiencing an opioid overdose within the next six months. Our objectives were to identify the proportion of patients ≥ 55 years discharged from the emergency department (ED) with a prescription opioid who were at risk for an opioid overdose as measured by CIP-RIOSORD, and to determine their CIP-RIOSORD risk class (or average predicted probability for an overdose). This study was a secondary analysis of data previously collected on patients returning to the ED for pain. Of the 85 patients included in this analysis, 17 (20%) were given an opioid prescription at ED discharge. Seven (41%) of these patients were at risk for an opioid overdose and met at least one CIP-RIOSORD predictive factor (range 1–3). The average CIP-RIOSORD risk class was 5 (patients' risk class ranged from 4 to 7), translating to a 29.8% average predicted probability of experiencing an overdose within six months (patients' predicted probability for an overdose ranged from 15.1% to 83.4%). Our findings illustrate that a considerable proportion of older ED patients discharged with a prescription opioid have a high predicted probability for an overdose within 6 months.